Pendampingan UMKM Kelurahan Mlati Baru, Kecamatan Timur, Kota Semarang, Melalui Pemasaran Digital: Pendampingan UMKM Kelurahan Mlati Baru, Kecamatan Timur, Kota Semarang, Melalui Pemasaran Digital - Widyakto, Adhi; Suryawardana, Edy; Souisa, Johanis; Riyanto, Sugeng (DIMASEKA, 2023)
The purpose of this community service activity is to help increase sales for MSMEs in the new Mlati Village affected by the COVID 19 pandemic. With this pandemic condition, MSMEs are required to survive in order to avoid bankruptcy. The method used in this community service activity is by providing direct training with tutorials in the field by teaching how to apply digital marketing or online marketing. The expected result is that the MSME product market in Mlati Baru Village gets a wider market reach, of course, with products that are recognized and easily accessible by consumers.